Determination of Most Frequent Emergencies in Patients with Fixed and Removable Orthodontic Appliances at Tertiary Care Dental Hospital - shah, Syed Salman; Syed, Kawish; Ul islam, Zafar; Adil, Shahab (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES: To determine the frequency of emergencies in patients with fixed and removable orthodontic appliances at tertiary care dental hospital. METHODOLOGY: A questionnaire was designed for this descriptive cross-sectional study to be filled by the clinician (L3/L4 FCPS resident) at the end of addressing every orthodontic emergency. Sampling was done under consecutive non-probability protocols. Descriptive statistics were applied to determine the frequency of different orthodontic emergencies, and Pearson’s chi-square test was applied to determine association of emergencies with gender and etiology of emergency (patient related vs operator related). Data was analyzed on SPSS version 20. RESULTS: A total of 175 patients reported with orthodontic emergencies. The sample comprised 38.3% males and 61.7% females. Most frequent orthodontic emergency reported was deboned brackets in fixed appliances, while the most common emergency in removable appliances was traumatic PNAM. A statistically significant association (Pearson’s Chi Square=4.74, Cramer’s V=0.165, p=0.029) was seen for removable and fixed appliance emergencies with males and females. CONCLUSION: Most frequent fixed appliance orthodontic emergencies were deboned brackets while for removable appliance emergencies were trauma due to PNAM. Emergencies with removable appliances were mostly due to the operator related factors, while in fixed appliances patient related factors were dominating.